Metaphoric resonance in Shakespearean tragedy - Stagman, Myron (Cambridge Scholars, 2010)
Shakespearean symbolism. An occasional prefigurement and echo was hardly unknown before Shakespeare. But the vast echoism -- continuing forward and backward references -- employed in some of Shakeapeare's tragedies, was rare if not unknown before him. Who, even now, sets up networks of metaphoric and symbolic vibrations underneath the surface story? thereby stressing themes and characterizations poetically, economically, subliminally. The phenomenon of Metaphoric Resonance is described wi ...